2020
DOI: 10.1101/2020.05.25.20111716
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychological impact of Covid-19 lockdown in India: Different strokes for different folks

Abstract: The psychological impact of the lockdown due to the Covid-19 pandemic are widely documented. In India, a family-centric society with a high population density and extreme social stratification, the impact of the lockdown might vary across diverse social groups. However, the patterning in the psychological impact of the lockdown among sexual minorities and persons known to be at higher risk of contracting Covid-19 is not known in the Indian context. We used mixed methods (online survey, n=282 and in-depth inter… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 51 publications
2
18
2
1
Order By: Relevance
“…According to Kruttschnitt and Gartner's (2003) review of research on women's imprisonment, female responses to imprisonment are similar to those found in male prisoners, although women tend to be more COVID-19 LOCKDOWN active in choosing their patterns of adjustment. Second, we found that whereas people in lockdown thought less often about missing sex than did first-time prisoners, who are deprived of heterosexual relations, our study does not capture the longing for homosexual relations that have been identified in some recent research on the Covid-19 lockdown (Sharma & Subramanyam, 2020). Finally, at the time of data collection, the lockdown sample had spent considerably less time in confinement than the prison sample, and so they may not have had sufficient time to adapt to their situation.…”
Section: Strengths and Limitationscontrasting
confidence: 65%
See 2 more Smart Citations
“…According to Kruttschnitt and Gartner's (2003) review of research on women's imprisonment, female responses to imprisonment are similar to those found in male prisoners, although women tend to be more COVID-19 LOCKDOWN active in choosing their patterns of adjustment. Second, we found that whereas people in lockdown thought less often about missing sex than did first-time prisoners, who are deprived of heterosexual relations, our study does not capture the longing for homosexual relations that have been identified in some recent research on the Covid-19 lockdown (Sharma & Subramanyam, 2020). Finally, at the time of data collection, the lockdown sample had spent considerably less time in confinement than the prison sample, and so they may not have had sufficient time to adapt to their situation.…”
Section: Strengths and Limitationscontrasting
confidence: 65%
“…Other studies have similarly noted a disruption to social ties during lockdown (e.g., Roy et al, 2020;Sharma & Subramanyam, 2020).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…When community spread became evident in the rapid spread of the disease, cities and states started taking such measures as quarantines and increased testing. However, the most stringent measure, a complete national lockdown for 21 days, was announced on March 24th with very little notice and eventually extended to May 3rd and has been applauded by the World Health Organization envoy Dr. Nabarro as “early, far‐sighted and courageous” (Sharma, 2020). According to Oxford University's Government Response Tracker data, India's response is one of the most stringent, with a Stringency Index score of 97 on a scale that ranges from 0 to 100 and reflects seven different measures (Figure 1).…”
Section: Public Health Responses To Covid‐19 In India: An Overviewmentioning
confidence: 99%
“…The lockdown was further extended until May 3rd, with conditional relaxations [3]. While the lockdown was intended to curb the spread of the virus, it had psychological ramifications on the citizens [4][5][6][7]. The self-isolation and restrictions on physical mobility due to the lockdown caused major disruptions to routines in life and hindered the ability to meet regular responsibilities-potentially affecting the physical and mental health of individuals.…”
Section: Introductionmentioning
confidence: 99%